Computer-human interaction : cognitive effects of spatial interaction, learning, and ability : 25th Australian Computer-Human Interaction Conference, OzCHI 2013, Adelaide, SA, Australia, November 25-29, 2013. Revised and extended papers /: cognitive effects of spatial interaction, learning, and ability : 25th Australian Computer-Human Interaction Conference, OzCHI 2013, Adelaide, SA, Australia, November 25-29, 2013. Revised and extended papers. (2015) - Unknown
No abstract available